2019–2020 Florida Citrus Production Guide: Tristeza Decline - Ozgur Batuman; Amit Levy; Mark E. Hilf; Peggy J. Sieburth; William O. Dawson; Ronald H. Brlansky (EDIS)
Citrus tristeza virus (CTV) is a major cause of the decline and eventual death of trees on sour orange rootstocks. This 2-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by O. Batuman, A. Levy, M. E. Hilf, P. J. Sieburth, W. O. Dawson, and R. H. Brlansky, and published by the Plant Pathology Department, March 2019.